The role of Institutions in Economic Development : case of Kazakhstan - Sidorova, Valeriya (2019)
AbstractThere is little evidence in the academic literature on this topic of economic institutions effect of the economic development in Kazakhstan. In this thesis we address this particular problem and identify that the institutions closely correlated with the economic growth in Kazakhstan. We start with a general overview of institutional economic field, make a review of its theories, summarise the results of the most outstanding works in the field and identify potential problems. We characterise Kazakhstan economy and observe positive development in terms of GDP per capita growth, inflation and unemployment reduction. Finally, using ordinary least squares we estimate the relationship between institutional indicators and real output per capita. The results show that control of corruption, government efficiency, rule of law and regulation quality are crucial for economic growth in Kazakhstan. Political stability and freedom of speech (voice and accountability) do not influence the economic growth in Kazakhstan. Keywords: Corruption, Economic growth, Institutions, Kazakhstan, Institutional economicsJEL classification: O430, O530, P260